Lines of common bean originating from the cross ’Ouro Negro’ x ’Pérola’ comprising favorable agronomic characteristics - Melo, Carlos Lásaro Pereira de; Carneiro, José Eustáquio de Souza; Carneiro, Pedro Crescêncio Souza; Cruz, Cosme Damião; de Barros, Everaldo Gonçalves; Moreira, Maurílio Alves (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to obtain high yielding common bean lines with "Carioca" type grains, resistant to anthracnose, rust and angular leaf spot. Colletotrichum lindemuthianum race 89 was artificially inoculated in 400 F7:8 progenies originated from 40 F3:7 families previously selected in the population 'Ouro Negro' x 'Pérola'. Lines resistant to race 89 were further inoculated with C. lindemuthianum races 73 and 81 and a mixture of six Uromyces appendiculatus races. Field evaluations were performed in Viçosa and Coimbra, MG, Brazil, using a triple 9x9 lattice design and productivity of grains, severity of angular leaf spot and grain aspect were evaluated. Forty two lines resistant to C. lindemuthianum and U. appendiculatus were identified. Ten lines comprising "Carioca" type grains, as productive as commercial cultivar Pérola and resistant to the anthracnose, rust and angular leaf spot were selected.